Feeding habits and length-weight relationship of Acentrogobius viridipunctatus (Cuv. & Val.) from Karachi coast - Hoda, S M Shamsul (Indian Journal of Fisheries, 2011)
Although feeding habits and relative condition factors of different species of gobiid fishes in relation to habitat, seasons, sizes, maturity stages and sexes have been studied by Sueyhiro (1942), Khoo (1966), Mutsaddi and Bal (1969), Hesthagen (1971), Shiogaki and Dotsu (1977), Hayashi and Goto, (1979) and Sarker et al. (1980), but no information is available from Pakistan. Hence an attempt has been made to present the details of feeding habits of Acentrogobius viridipunctatus from Pakistan coast